Protocol for an economic evaluation alongside the University Health Network Whiplash Intervention Trial: cost-effectiveness of education and activation, a rehabilitation program, and the legislated standard of care for acute whiplash injury in Ontario - van der Velde Gabrielle; Côté Pierre; Bayoumi Ahmed M; Cassidy J David; Boyle Eleanor; Shearer Heather M; Stupar Maja; Jacobs Craig; Ammendolia Carlo; Carette Simon; van Tulder Maurits (BMC, 2011)
Abstract Background Whiplash injury affects 83% of persons in a traffic collision and leads to whiplash-associated disorders (WAD). A major challenge facing health care decision makers is identifying cost-effective interventions due to lack of economic evidence. Our objective is to compare the cost-effectiveness of: 1) physician-based education and activation, 2) a rehabilitation program developed by Aviva Canada (a group of property and casualty insurance providers), and 3) the legislated standard of care in the Canadian province of Ontario: the Pre-approved Framework Guideline for Whiplash developed by the Financial Services Commission of Ontario. Methods/Design The economic evaluation will use participant-level data from the University Health Network Whiplash Intervention Trial and will be conducted from the societal perspective over the trial's one-year follow-up. Resource use (costs) will include all health care goods and services, and benefits provided during the trial's 1-year follow-up. The primary health effect will be the quality-adjusted life year. We will identify the most cost-effective intervention using the incremental cost-effectiveness ratio and incremental net-benefit. Confidence ellipses and cost-effectiveness acceptability curves will represent uncertainty around these statistics, respectively. A budget impact analysis will assess the total annual impact of replacing the current legislated standard of care with each of the other interventions. An expected value of perfect information will determine the maximum research expenditure Canadian society should be willing to pay for, and inform priority setting in, research of WAD management. Discussion Results will provide health care decision makers with much needed economic evidence on common interventions for acute whiplash management. Trial Registration http://ClinicalTrials.gov identifier NCT00546806 [Trial registry date: October 18, 2007; Date first patient was randomized: February 27, 2008]